IMPROVING THE QUALITY OF HUMAN RESOURCES FROM A SOCIO-ECONOMIC PERSPECTIVE IN THE GLOBALIZATION ERA - M Usman Maliki; Alditya Aris Rinandy; Amaliah Khairunissa (Jurnal Manajemen, 2023)
The article entitled improving the quality of human resources from a socio-economic perspective in the era of globalization discusses the relationship between theory and phenomena to improve the quality of human resources with the support of the phenomenon of globalization. Increasing competence in the era of globalization must be addressed from the right perspective, especially how the method or method of development is carried out so that human resources can develop and grow according to needs. The purpose of writing this article is to find out and find solutions in the future in terms of improving the quality of human resources, where in this article references to Giddens' theory are used which are closely related to the concept of globalization. This article uses literature that does not collect data directly, but with various references that support the writing of this article. Data collection was carried out by recording information from references related to this article and related themes according to the purpose of the article. The Human Resources Variable is expected to develop by the globalization era with the concept of HR development consisting of 2 (two) types, namely informal and formal HR development.